1997
DOI: 10.1182/blood.v89.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Major Histocompatibility Complex Restriction Between Hematopoietic Stem Cells and Stromal Cells In Vivo

Abstract: Graft failure is a mortal complication in allogeneic bone marrow transplantation (BMT); T cells and natural killer cells are responsible for graft rejection. However, we have recently demonstrated that the recruitment of donor-derived stromal cells prevents graft failure in allogeneic BMT. This finding prompted us to examine whether a major histocompatibility complex (MHC) restriction exists between hematopoietic stem cells (HSCs) and stromal cells. We transplanted bone marrow cells (BMCs) and bones obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 104 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…17 We have found that IBM-BMT not only allows us to use low-dose irradiation as a pre-conditioning regimen 17 but also helps to suppress GVHD, 18 as this IBM-BMT method can efficiently recruit donor-derived stromal cells [including mesenchymal stem cells (MSCs)], which can support donor-derived haemopoietic stem cells. 1,[19][20][21] In addition, it has recently been shown, even in humans, that stromal cells or MSCs suppress GVHD. 22,23 The thymus is an organ in which T cells can be induced to differentiate from precursor T cells.…”
Section: Introductionmentioning
confidence: 99%
“…17 We have found that IBM-BMT not only allows us to use low-dose irradiation as a pre-conditioning regimen 17 but also helps to suppress GVHD, 18 as this IBM-BMT method can efficiently recruit donor-derived stromal cells [including mesenchymal stem cells (MSCs)], which can support donor-derived haemopoietic stem cells. 1,[19][20][21] In addition, it has recently been shown, even in humans, that stromal cells or MSCs suppress GVHD. 22,23 The thymus is an organ in which T cells can be induced to differentiate from precursor T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that syngeneic and allogeneic BMC coresided in common cellular clusters and adhesion appeared to improve BMC survival, it is possible that antigen disparity does not affect BMC interaction with stromal cells. Alternatively, deficient seeding of donor cells in recipient BM stroma could be restricted by antigenic barriers [10], as substantiated by inhibition of cobblestone formation in stromal cell cultures [11]. To elaborate on the characteristics and restrictions of donor BMC adhesion to recipient BM stroma, the seeding efficiency of syngeneic versus allogeneic lineage + BMC and lineage -HSPC was quantitatively assessed in situ.…”
Section: Introductionmentioning
confidence: 99%
“…Six months after BMT, the graft acceptance was examined, and the percentages of the donor cells in the peripheral blood were analyzed using a FACS. HSCs should show a better proliferative response than C3H HSCs, as we have previously shown [13]. It should be noted that all the pancreas allografts are accepted when more than 1% of allogeneic cells are detected in the PB of the recipients.…”
Section: Discussionmentioning
confidence: 81%